2005
DOI: 10.1183/09031936.04.00116203
|View full text |Cite
|
Sign up to set email alerts
|

Asthma: prevalence and cost of illness

Abstract: The purpose of this study was to estimate the prevalence and cost of illness of asthma in Germany by retrospectively analysing routine health insurance data.This analysis investigated claims data from all insured persons of six large sickness funds. Insurants with asthma were identified via the International Classification of Diseases (ninth revision) diagnosis and the Anatomical Therapeutic Chemical Classification System Code for regular medication prescriptions. Costs for hospital care, medication and sick b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
87
3
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 29 publications
13
87
3
8
Order By: Relevance
“…This figure is similar to the 81%, 84%, and 89% found in Turkey, Germany, and Australia, respectively [10,16,22], but higher than other studies which reported that medication costs corresponded to a range between 30 and 47% direct costs of asthma care [12][13][14]. The differences in prescription costs noted may be due to differences in the types of medication given to the patients, doses of medication required by each patient, and the severity of their asthma.…”
Section: Discussionsupporting
confidence: 61%
“…This figure is similar to the 81%, 84%, and 89% found in Turkey, Germany, and Australia, respectively [10,16,22], but higher than other studies which reported that medication costs corresponded to a range between 30 and 47% direct costs of asthma care [12][13][14]. The differences in prescription costs noted may be due to differences in the types of medication given to the patients, doses of medication required by each patient, and the severity of their asthma.…”
Section: Discussionsupporting
confidence: 61%
“…The annual cost of asthma has recently been estimated to be J2.7 billion in Germany [9] and J1.5 billion in France. In the UK, asthma costs the National Health Service an average of £889 million per yr [10].…”
mentioning
confidence: 99%
“…Many people suffer from allergies and the occurrence of allergies is considered one of the major medical problems in the world (Rachele, 1980;Stock et al, 2005;Eder et al, 2006;Russell, 2006). The daily reports of outdoor airborne pollen and spores are used as an indicator of the threat of exposure to a variety of allergens for people at high risk (Frenz, 2000a;Frenz et al, 1998;Giberson et al, 1997).…”
mentioning
confidence: 99%